domOS: an “Operating System” for Smart Buildings - Dongo, Junior; Gabioud, Dominique; Laadhar, Amir; Meyer, Martin; Nielsen, Brian; Revaz, Frédéric; Thomsen, Christian (CLIMA 2022 conference, 2022)
Smart energy services deployed in buildings have the potential to increase their energy efficiency and to turn them into active nodes of energy grids, with limited costs and in the short term. Today, smart services are deployed by manufacturers of energy appliances as independent silo solutions. The lack of a common approach prevents the deployment of unified multi-appliance, multi-service solutions. This paper presents the domOS ecosystem specification, a guideline for a unified organisation of energy services where multiple applications can access multiple on-line appliances and devices, if permitted. The specification leverages legacy IoT technologies and can be implemented with a limited effort on any existing IoT platform. A compliant IoT platform acts as an “operating system” for the building, effectively decoupling the application plane and the building infrastructure plane. The domOS ecosystem specification builds upon the Web of Things (WoT) architecture defined by W3C. Compliant buildings feature a digital nameplate called Building Description (BD). The BD is a document readable by machines and humans that contains relevant metadata (e.g., construction type, size, energy system…) and provides handles to monitor and control local energy processes. The domOS ecosystem specification leads to a unified and standardised approach of energy services in buildings.